PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA APARTEMEN PAVILION JAKARTA - Bonifasius M.H Nainggolan; Efendi; Yosi Anita Adveni (LPPM Universitas Asa Indonesia, 2020)
This research was conducted on staff of Apartemen Pavilion Jakarta. This study aims to determine the effects of transformational leadership style, work motivation and job satisfaction to job performance at Apartemen Pavilion Jakarta. This study used primary data obtained from the questionnaire by purposive sampling method. Samples of data were obtained from 150 respondents consisting of staff of Apartemen Pavilion Jakarta. The variables in this study were transformational leadership style (X1), work motivation (X2), job satisfaction (X3), and job performance (Y). The author used quantitative descriptive method and the analysis method used in this study is multiple linear regression analysis. Transformational leadership style, work motivation and job satisfaction provide a significant effect on job performance at Apartemen Pavilion Jakarta.